Boracic polyethylene/polyethylene wax blends and open-cell nickel foams as neutron-shielding composite. (February 2018) - Zhang, Yun; Chen, Feida; Tang, Xiaobin; Huang, Hai; Chen, Tuo; Sun, Xiangyu
This work shows that mechanical properties, thermal conductivity, and secondary gamma-ray shielding ability can be significantly improved when open-cell nickel foams are embedded into the shielding composites. The boracic polyethylene/polyethylene wax blends and open-cell nickel foam composites (PPNM) are designed and prepared by permeating homogeneous mixed melt fillers into open-cell nickel foams. The ratio of polyethylene and polyethylene wax is investigated to achieve higher filling rate. The quasi-static compressive response of PPNMs and polyethylene/polyethylene wax blends is measured, and the crystallization properties are studied by differential scanning calorimetry. The neutron and secondary gamma-ray shielding abilities of PPNMs are also simulated based on Monte Carlo particle transport method. Results show that the compression strength of PPNMs with boron carbide is slightly improved when compared with polyethylene/polyethylene wax blends. The nickel foams in PPNM composites improve the energy-absorbing efficiency by 30%. The thermal conductivity of PPNMs is 300% higher than polyethylene/polyethylene wax. The calculated results show that neutron-shielding abilities of PPNMs increase as content of boron carbide increases. Moreover, secondary gamma-ray shielding ability of PPNMs containing boron carbide is obviously higher than polyethylene/polyethylene wax. The PPNMs containing boron carbide neutron-shielding materials are proved to have good thermal conductivity, mechanical properties, and radiation-shielding ability.